Improving cochlear implant properties through conductive hydrogel coatings - Hassarati,RT; Dueck,WF; Tasche,C; Carter,PM; Poole-Warren,LA; Green,RA (IEEE Transactions on Neural Systems and Rehabilitation Engineering, 2014)
Conductive hydrogel (CH) coatings for biomedical electrodes have shown considerable promise in improving electrode mechanical and charge transfer properties. While they have desirable properties as a bulk material, there is limited understanding of how these properties translate to a microelectrode array. This study evaluated the performance of CH coatings applied to Nucleus Contour Advance cochlear electrode arrays. Cyclic voltammetry and biphasic stimulation were carried out to determine electrical properties of the coated arrays. Electrical testing demonstrated that CH coatings supported up to 24 times increase in charge injection limit. Reduced impedance was also maintained for over 1 billion stimulations without evidence of delamination or degradation. Mechanical studies performed showed negligible effect of the coating on the pre-curl structure of the Contour Advance arrays. Testing the coating in a model human scala tympani confirmed that adequate contact was maintained across the lateral wall. CH coatings are a viable, stable coating for improving electrical properties of the platinum arrays while imparting a softer material interface to reduce mechanical mismatch. Ultimately, these coatings may act to minimize scar tissue formation and fluid accumulation around electrodes and thus improve the electrical performance of neural implants. © 2013 IEEE.